THE EFFECT OF DISCIPLINE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE IN THE MINISTRY OF RELIGION OFFICE SOUTH TANGERANG CITY - Ratna Dumilah; Asridah Warni Tanjung; Nindie Ellesia (Yayasan Education and Social Center, 2023)
This study aims to determine the effect of discipline and work environment on employee performance at the Office of the Ministry of Religion of South Tangerang City partially and simultaneously. This study uses quantitative methods with data collection tools using a questionnaire. The total population at the Office of the Ministry of Religion of South Tangerang City is 65 people. Sampling using a saturated sample technique that takes the entire population of employees at the Office of the Ministry of Religion of South Tangerang City, amounting to 65 people. Data analysis techniques using regression analysis, correlation coefficient analysis, analysis of the coefficient of determination, and hypothesis testing. The results of this study indicate that the variables of discipline and work environment partially affect the performance of employees at the Office of the Ministry of Religion of South Tangerang City. Then, the variables of discipline and work environment simultaneously affect the performance of employees at the Office of the Ministry of Religion of South Tangerang City.